Intra‐ and inter‐individual differences in human sperm DNA methylation. (18th April 2016) - Dere, E.; Huse, S.; Hwang, K.; Sigman, M.; Boekelheide, K.
Summary: There is growing evidence that sperm DNA methylation is important in maintaining proper sperm health and function. Previous studies have associated sperm DNA methylation levels with sperm quality and function, however, little is known regarding the intra‐ and inter‐individual variability in sperm methylation levels. This study characterizes this variation. Sperm epigenetic differences between successive semen samples from 12 patients were examined to identify the intra‐ and inter‐individual differences globally across the genome, and in specifically defined genomic regions using the Illumina Infinium HumanMethylation450 BeadChips. Methylation analysis identified a bimodal distribution in the methylation levels that were non‐uniformly distributed across the different genomic regions. The methylation levels were highly correlated in both the intra‐ and inter‐individual comparisons. The intra‐individual methylation levels were more highly correlated than the inter‐individual comparison both globally and across the defined genomic regions, demonstrating that sperm DNA methylation levels are relatively stable between semen sample collections.